Constructing a mathematical model of the gas-dynamic separation for designing energy-saving vortex separators - Knaub, Ludmila; Maslich, Natalia; Rabochaya, Tatiana (Eastern-European Journal of Enterprise Technologies, 2018)
We developed a mathematical model of the separation process of heterogeneous polydisperse mixtures in the proposed energy saving vortex separators, which is represented by a system of differential equations linking parameters of the process control to the geometric dimensions of device. We showed the possibility to solve a mathematical model based on the grid method for the determination of initial parameters and control parameters of the separation process, as well as for determination of coordinates of components with different shapes, densities, aerodynamic and gas dynamic properties. This will significantly reduce time for calculations of gas-dynamic vortex separators of any mixtures. We proved the reliability of the calculation based on the grid method by comparing it with the results of the experiment. This makes it possible to calculate and design vortex separators without expensive calibrating sieves and energy-intensive vibration equipment. We established the region of a change in the generally accepted coefficients of efficiency and precision of the separation of a flour mixture, which determine the presence of harmful components in a resulting product and the content of high quality components in waste, which should not exceed 2 %. We detected boundary values of the coefficients of efficiency hе=88 % and precision hs=0.9 of mixtures of flour of the highest grade, the first grade, and the second grade, which could be used as the initial data in the design of vortex separators. We proved the possibility to control the separation process by changes in gas-dynamic parameters of a heterogeneous mixture at the inlet to a separator. This will make it possible to change the velocity of redistribution of components of a mixture and to obtain necessary indicators of a resulting product with a predetermined degree of purity. The research results proved the possibility for implementing vortex separators into industrial production. This will significantly reduce the cost of preparation of raw materials in grain processing, coal, and other fields, as well as in the production of dolomite, construction materials, etc. Using the vortex gas-dynamic separators in technological processes would improve production environment and reduce the cost of maintenance and repair, since they operate in a closed cycle and do not contain expensive calibrating sieves and electric drives.